2002
DOI: 10.1093/jn/132.7.1935
|View full text |Cite
|
Sign up to set email alerts
|

The Degree of Methylation Influences the Degradation of Pectin in the Intestinal Tract of Rats and In Vitro

Abstract: We investigated the degradation, metabolism, fate, and selected effects of pectin in the intestinal tract of rats. Conventional and germfree rats were fed for 3 wk diets containing 6.5% pectin (degree of methylation 34.5, 70.8 and 92.6%, respectively) or pectin-free diets. Pectin passes the small intestine as a macromolecule. The molecular weight distribution of pectins isolated from intestinal contents of germfree rats were unaffected by diet. No or very little galacturonan was found in cecum, colon or feces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
111
5
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 34 publications
20
111
5
2
Order By: Relevance
“…Decreased overall food intake in pectin-fed rats was accompanied with increased satiety and with increased circulating concentrations of the gut satiety hormones (1). In contrast, several studies have suggested that pectin does not influence food intake and growth rate (7,9).…”
Section: Discussionmentioning
confidence: 88%
“…Decreased overall food intake in pectin-fed rats was accompanied with increased satiety and with increased circulating concentrations of the gut satiety hormones (1). In contrast, several studies have suggested that pectin does not influence food intake and growth rate (7,9).…”
Section: Discussionmentioning
confidence: 88%
“…It has also been suggested that the production of butyrate from these fibres could protect against the initial stages of colon carcinogenesis [92]. Butyrate, as suggested, is able to arrest the growth of neoplastic colonocytes and inhibit the preneoplastic hyperproliferation induced by the several tumour initiators and promoters [93,94]. This type of fibre also has been suggested to be paramount to carcinogenesis by changing from propionate to butyrate, as observed in animals fed hydrolysed guar [95].…”
Section: Anti-cancer Mechanism By Rice By-products Dietary Fibrementioning
confidence: 99%
“…It is also used as ingredients in the prevention of coronary heart disease, colon cancer, hypercholesterolemia [11]- [14]. Physiological (fermentability by microbiota) and functional properties (gelation or biding of metal ions) of pectin are different, relying on its structural parameters like molecular weight, degree of methylation (DM), and distribution of free and methoxylated carboxyl groups within the galacturonan chains [15]. Few studies have been investigated the effects of purified pectin on fermentation pattern and gut microbiota.…”
Section: Introductionmentioning
confidence: 99%